QUALITY OF LIFE IN CHILDREN WITH VISION DISORDERS - L.V. Nefedovskaya ("Paediatrician" Publishers LLC, 2009)
The aim of this trial was to evaluate the peculiarities of quality of life (QL) of blind and purblind children, educated in specialized schools. 64 schoolchildren from specialized correction school and 78 schoolchildren from boarding school of Tatarstan Republic in age 8-12 and 13-18 years old took part in this trial. Instrument of this trial was Russian version of general questionnaire Pediatric Quality of Life Inventory - PedsQL4.0. Results of study showed, that quality of life of blind and purblind children was lower then in their healthy coevals, according to opinion of children, their parents and teachers. On the other hand, quality of life of children with vision disorders, educated in different types of correction schools, did not differ. Key words: quality of life, blind and purblind children. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):10-12)